الدور الوسيط لرأس المال النفسي في العلاقة بين جودة حياة العمل والإبداع التنظيمي: دراسة حالة موظفي مفوضية الإتحاد الإفريقي بأديس بابا.: The mediating role of psychological capital in the relationship between quality of work life and organizational creativity: a case study of the African Union Commission employees in Addis Ababa. - واري زكرياء; واري حسين; لفقير علي (Journal of North African Economies, 2025)
This study aims to identify the relationship between the quality of work life and organizational creativity, through psychological capital as a mediating variable, and to achieve this, we prepared a questionnaire and distributed it to a random sample consisting of (82) senior officers, they belong to the Department of Economic Development, Trade, Industry and Mining of the African Union Commission in Addis Ababa, For the statistical treatment of the data, we used structural equations modeling by the partial least squares method (PLS-SEM), and the study concluded that there is a statistically significant impact of the quality of work life on organizational creativity; There is a statistically significant impact of the quality of work life on psychological capital; There is a statistically significant effect of psychological capital on organizational creativity; There is a statistically significant impact of the quality of work life on organizational creativity with the presence of psychological capital as a mediating variable.